2020
DOI: 10.3389/fmicb.2020.00301
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Talk Between Gut Microbiota and Lungs in Common Lung Diseases

Abstract: Emerging findings indicate there is a vital cross-talk between gut microbiota and the lungs, which is known as gut-lung axis. The gut disturbances in lung diseases including allergy, asthma, chronic obstructive pulmonary disease, cystic fibrosis and lung cancer were observed by extensive studies. Investigating how gut microbiota impact other distant organs is of great interest in recent years. Although it has not been fully understood whether the disturbance is the cause or effect of lung diseases, alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
264
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(288 citation statements)
references
References 121 publications
6
264
0
4
Order By: Relevance
“…Of note, other probable mechanisms have been proposed, which are not mutually exclusive, to explain the effect of the intestinal beneficial microbes on the respiratory antiviral immunity. There is evidence that some microbial-associated molecular patterns (MAMPs) derived from the intestinal microbiota can be adsorbed and transported to extraintestinal sites where they stimulate pattern recognition receptors (PRRs) expressed in non-immune and immune cells influencing the immune responses ( 58 , 59 ). In addition, microbial metabolites that are adsorbed in the intestine have been associated to the differential modulation of respiratory immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, other probable mechanisms have been proposed, which are not mutually exclusive, to explain the effect of the intestinal beneficial microbes on the respiratory antiviral immunity. There is evidence that some microbial-associated molecular patterns (MAMPs) derived from the intestinal microbiota can be adsorbed and transported to extraintestinal sites where they stimulate pattern recognition receptors (PRRs) expressed in non-immune and immune cells influencing the immune responses ( 58 , 59 ). In addition, microbial metabolites that are adsorbed in the intestine have been associated to the differential modulation of respiratory immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Following airway immune stimulation, T-cells are activated in the GALT and MLN, move to the respiratory epithelium and provide protection and anti-inflammatory action. The SCFAs from the intestine reach the lungs and suppress inflammation [ 9 , 12 , 13 ].…”
Section: The Gut-lung Axismentioning
confidence: 99%
“…In addition, the interaction between the intestine and the lungs plays an important role in pulmonary microbiome eubiosis and immunomodulation [ 8 , 9 , 10 ]. It then becomes important to investigate the role of: (a) pathogenic microbes that cause or contribute to disease development and/or progression, (b) commensal microbes that do not cause disease, (c) neutral or beneficial host interaction bacterial microbiota studies, (d) the recent reassessment of viruses and fungi [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A randomized-controlled study of children suffering from acute lung injury found signi cantly lower levels of in ammatory factors and less small bronchial obstruction in children treated with probiotics when compared to placebo-treated controls, whose in ammatory factors did not drop as rapidly and whose pulmonary function was still limited after 10 days (15). Although some aspects of the interaction between the intestinal-and the lung microbiome have been described, the complex cross-talk, the causality between lung diseases and gut microbiota is still underexplored (16).…”
Section: Introductionmentioning
confidence: 99%